Amiodarone-associated bilateral optic neuropathy: a case report: Bilateralna optikonevropatija po zdravljenju z amiodaronom - prikaz primera - Bečić Turkanović, Anela; Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Purpose: Amiodarone is a commonly prescribed anti-arrhythmic drug; however, its use is limited by many adverse effects. Amiodarone causes lung, thyroid gland, skin, central nervous system, liver, and eye disorders. Corneal microdeposits are the most common ocular adverse effects, while more serious tissue damage such as optic neuropathy can also occur. The aim of this report was to describe a case of a toxic optic neuropathy, which is one of the adverse effects of amiodarone treatment.Case report: This is a case report of a 51-year-old patient hospitalized at the Department of Ophthalmology University Medical Center Maribor because of blurred vision, first in his right eye and later in his left eye. Three months before admission, the patient began treatment with amiodarone because of arrhythmia after acute pericarditis. The patient underwent a complete ophthalmic examination and other tests for all known optic neuropathy causes. The patient initially presented with blurred vision in his right eye, and also in his left eye after 7 days. Except for corneal micro-deposits and optic disc edema, the results of an ophthalmic exam were normal. Static and kinetic visual field examinations showed bilateral visual field defects. Fluorescein angiography showed bilateral fluorescein dye leakage from the optic disc. Amiodarone treatment was terminated on the 7th day of hospitalization, and the patient reported improvement of vision in subsequent weeks. The edema in his left optic disc resorbed at 3.5 weeks and in his right optic disc at 5 weeks after termination of amiodarone treatment. Kinetic and static perimetry showed improvement in the visual field 10 weeks after the termination of amiodarone treatment.Conclusions: Toxic optic neuropathy had a similar clinical course as non-arteritic anterior ischemic optic neuropathy. Prompt diagnosis is crucial because treatment with amiodarone can prevent irreversible visual impairment. Because of the frequent clinical use of amiodarone, and despite the low incidence of toxic optic neuropathy, regular annual follow-up examinations should be performed.
Keywords: Amiodarone; optic neuropathy; visual acuity; visual field